Refugee Motherhood and Mothering: Adversities, Resilience, and Agency - May-Kyawt, Ame Khin (Journal of the Motherhood Initiative for Research and Community Involvement, 2025)
Through using intersectionality as a critical framework, this article focuses on refugee mothers’ challenges, resilience, and agency within the context of forced migration from Southeast Asia to Canada. It explores the unique context of Karen refugee mothers who were relocated to Canada following their initial displacement from their villages in Myanmar (formerly known as Burma) to various refugee camps on the Thailand-Burma border and asks the following question: How do Karen refugee mothers deal with adversities in the resettlement process, and do they regard their gendered roles positively or negatively? I conducted qualitative, semi-structured, in-depth interviews with ten first-generation Karen refugee women residing in London, Southwestern Ontario. The interviews investigate how refugee mothers feel about their gender roles regarding motherhood, mothering, and responsibilities and how they renegotiate gender roles and remake mothering practices while dealing with problems in the settlement process. My study aims to fill the knowledge gap about minority refugee mothers’ resettlement narratives in a culturally grounded family context. Based on the findings, I argue that it is not possible to fully understand women’s agencies in the context of forced migration without looking at their stressors and other aspects of intersecting identities, such as mothers, othermothers, gender roles, race, ethnicity, immigration status, socioeconomic status, and class.